Method for repairing or recycling elastic membrane
By using polymer latex containing carboxylated conjugated dienenitrile latex polymer and ethylene oxide functional-based latex polymer, combined with thermal reprocessing technology, the problem of irreversible damage of the existing elastic film is solved, and the elastic film is realized. Self-healing, repairing and recycling.
Patent Information
- Application Number
- CN201980096411.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-05-17
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2039-05-17
AI Technical Summary
The existing elastic membranes need to be cross-linked during the preparation process, resulting in irreversible damage, inability to repair and recycling, and waste of resources.
The elastic film is repaired or recovered by thermal reprocessing technology using polymer latex composed of carboxylated conjugated dienenitrile latex polymer and latex polymer containing ethylene oxide functional groups.
The self-healing, repair and recycling of elastic membranes is achieved, avoiding resource waste and reducing production costs.
Smart Images

Figure CN113825604B_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to methods of repairing or recycling elastic films and in particular, but not exclusively, to the use of thermal reprocessing means to repair or recycle elastic films. In addition, the present invention relates to the use of a specific polymer latex to make elastic films made from aqueous dispersions of said polymer latex particles repairable and recyclable and also to allow said films to self-heal. Background of the Invention
[0003] According to current industry standards, elastic films, especially in dip molding applications, such as examination gloves, are made from compounds containing carboxylated nitrile latex (XNBR). In order to obtain the mechanical strength required for these elastic film application targets, some cross-linking of the film needs to be achieved during the preparation of the elastic film.
[0004] In order to obtain such crosslinked elastic films, several different concepts are available in the prior art. One possibility is that the compounds used to prepare the elastic film contain conventional sulfur vulcanization systems, such as sulfur in combination with accelerators such as thiurams and urethanes and zinc oxide.
[0005] Since sulfur vulcanization systems can cause allergic reactions, alternative concepts have been developed to make latex films curable. Another possibility is to include a crosslinking agent component in the compound, such as a multivalent cation, such as zinc oxide or other multifunctional organic compounds suitable for reacting with the functional groups on the latex particles to achieve chemical crosslinking. In addition, if the polymer latex carries a sufficient amount of self-crosslinking groups, such as N-hydroxymethylamide groups, sulfur vulcanization systems and / or crosslinking agents can be completely avoided.
[0006] All of these different concepts result in cross-linked elastic films, where the cross-linking is irreversible in nature, making these elastic films not easily recyclable, nor do they show any self-healing properties to make them repairable. For example, if any kind of defects such as pinholes occur during the elastic film preparation process due to the lack of self-healing properties of the film, these products need to be discarded, thereby generating non-reusable waste. In addition, if such elastic films are broken during their use, they cannot be repaired, resulting in irreversible destruction of the elastic film, thereby causing failure of the article containing such elastic films.
[0007] Therefore, there is a need in the industry for elastic films that have inherent self-healing properties and are potentially recyclable to reduce the unusable waste of such elastic films and avoid the ultimate failure of articles that include such elastic films.
[0008] WO 2017 / 209596 discloses a polymer latex for dipping applications, which includes two different types of latex particles. One latex particle is carboxylated, and the second latex particle contains ethylene oxide functional groups.
[0009] Therefore, the present invention seeks to provide a method for repairing or recycling an elastic film and selects a specific polymer latex so that the elastic film obtained from the polymer latex is repairable and recyclable. SUMMARY OF THE INVENTION
[0010] The present inventors surprisingly found an elastic film made of a polymer latex comprising:
[0011] (a) Particles of a carboxylated conjugated diene nitrile latex polymer (a), which may be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising:
[0012] - 15-99 wt% of a conjugated diene;
[0013] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0014] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0015] - 0-50 wt% of vinyl aromatic monomers; and
[0016] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0017] The weight percentages are based on the total monomers in the mixture.
[0018] Combined or combined with:
[0019] (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein
[0020] The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b).
[0021] The elastic film has self-healing properties and can therefore be repaired and recycled. This was not possible with the elastic films from the known prior art that were vulcanized with sulfur.
[0022] According to one aspect, the present invention relates to a method for repairing an elastic membrane or an article comprising an elastic membrane by the following steps:
[0023] a) providing a damaged elastic film or an article comprising a damaged elastic film, wherein the damaged elastic film has at least a surface to be reattached,
[0024] b) rejoining the surfaces of damaged membranes, and
[0025] c) heating or annealing the damaged elastic film at a temperature of 40° C. to 200° C. while maintaining the rejoined surfaces of the damaged film in close contact, wherein
[0026] The elastic film is made of a polymer latex comprising:
[0027] (a) particles of a carboxylated conjugated diene nitrile latex polymer (a), which can be obtained by free radical emulsion polymerization of a mixture comprising the following ethylenically unsaturated monomers:
[0028] - 15-99 wt% of a conjugated diene;
[0029] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0030] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0031] - 0-50 wt% of vinyl aromatic monomers; and
[0032] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0033] The weight percentages are based on the total monomers in the mixture.
[0034] Combined or combined with:
[0035] (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein
[0036] The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b).
[0037] According to another aspect, the present invention relates to a method for recovering an elastic film or an article comprising an elastic film by cutting, shredding or crushing the elastic film or article to form elastomeric particles, optionally blending the obtained particles with original elastomeric particles, and forming a recovered film or article by subjecting the particles to a pressure of 1-20 MPa and a temperature of 40° C. to 200° C., wherein
[0038] The elastic film is made of a polymer latex comprising:
[0039] (a) Particles of a carboxylated conjugated diene nitrile latex polymer (a), which may be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising:
[0040] - 15-99 wt% of a conjugated diene;
[0041] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0042] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0043] - 0-50 wt% of vinyl aromatic monomers; and
[0044] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0045] The weight percentages are based on the total monomers in the mixture.
[0046] Combined or combined with:
[0047] (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein
[0048] The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b).
[0049] According to another aspect, the present invention relates to the use of a polymer latex comprising:
[0050] (a) particles of a carboxylated conjugated diene nitrile latex polymer (a), which can be obtained by free radical emulsion polymerization of a mixture comprising the following ethylenically unsaturated monomers:
[0051] - 15-99 wt% of a conjugated diene;
[0052] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0053] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0054] - 0-50 wt% of vinyl aromatic monomers; and
[0055] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0056] The weight percentages are based on the total monomers in the mixture.
[0057] Combined or combined with:
[0058] (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein
[0059] The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b),
[0060] The elastic film obtained from the polymer latex is made self-healing, repairable and / or recyclable. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 The dried and cured films were shown to be cut into dumbbell-shaped specimens (25 ± 0.8 mm length, 6 mm width and 0.056-0.066 mm thickness).
[0062] Figure 2A dumbbell-shaped sample is shown strained to 1%, and the initial stress value is recorded as G0.
[0063] Figure 3 Shows a dumbbell-shaped specimen held at 1% strain and the stress value (G t ).
[0064] Figure 4 Stress relaxation tests obtained from Example 9 are shown.
[0065] Figure 5 Stress relaxation tests obtained from Example 10 are shown.
[0066] Figure 6 Stress relaxation tests obtained from Example 11 are shown.
[0067] Figure 7 Tensile testing of a self-healed dumbbell obtained from Example 22 is shown, compared to the results obtained for an uncut dumbbell obtained from the same cast film.
[0068] Figure 8 Tensile testing of a self-healed dumbbell obtained from Example 23 is shown, compared to the results obtained for an uncut dumbbell obtained from the same cast film.
[0069] Fig. 9 Tensile testing of a self-healed dumbbell obtained from Example 24 is shown, compared to the results obtained for an uncut dumbbell obtained from the same cast film.
[0070] Fig.10 Tensile testing of a self-healed dumbbell obtained from Example 25 is shown, compared to the results obtained for an uncut dumbbell obtained from the same cast film. DETAILED DESCRIPTION OF THE INVENTION
[0072] Polymer latexes making elastic films obtained therefrom self-healing, repairable and / or recyclable The polymer latex used according to one aspect of the present invention imparts self-healing properties to the elastic film obtained therefrom so that the elastic film is repairable and / or recyclable, the polymer latex comprising:
[0073] (a) particles of a carboxylated conjugated diene nitrile latex polymer (a), which can be obtained by free radical emulsion polymerization of a mixture comprising the following ethylenically unsaturated monomers:
[0074] - 15-99 wt% of a conjugated diene;
[0075] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0076] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0077] - 0-50 wt% of vinyl aromatic monomers; and
[0078] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0079] The weight percentages are based on the total monomers in the mixture.
[0080] Combined or combined with:
[0081] (b) particles of a latex polymer (b) comprising at least one oxirane functional group;
[0082] The monomer composition of the latex polymer (a) is different from the monomer composition of the latex polymer (b).
[0083] The term "combination or bonding" encompasses latexes in which latex polymer (a) and latex polymer (b) are present in the form of a physical mixture, such as a blend of two latex polymers, and latexes in which latex polymer (a) and latex polymer (b) exhibit any kind of chemical or physical interaction between latex polymer (a) and latex polymer (b) particles. According to the present invention, the combination or bonding of the latex polymer (a) particles with the latex polymer (b) particles can be achieved, for example, by one of the following measures:
[0084] (i) a mixture of ethylenically unsaturated monomers of latex polymer (a) is polymerized in a free radical emulsion polymerization in the presence of ethylene oxide functional latex particles (b);
[0085] (ii) preforming a polymer latex comprising particles of latex polymer (a) and a polymer latex comprising particles of latex polymer (b), and subsequently combining the two latexes; and
[0086] (iii) a mixture of ethylenically unsaturated monomers of latex polymer (a) is polymerized in a free radical emulsion polymerization in the presence of ethylene oxide functional latex particles (b) to form a first polymer latex, a second polymer latex comprising latex polymer (b) particles is preformed and the two latexes are subsequently combined, wherein the latex comprising ethylene oxide functional latex particles (b) present in the polymerization of the mixture of ethylenically unsaturated monomers of latex polymer (a) and the second polymer latex comprising component (b) particles may be the same or different.
[0087] The term "the monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b)" encompasses the monomers used to prepare latex polymer (a) being different from the monomers used to prepare latex polymer (b), or the monomers being the same but used in different relative amounts in preparing latex polymer (a) and latex polymer (b).
[0088] The polymer latex of the present invention may comprise:
[0089] (a) Particles of a carboxylated conjugated diene nitrile latex polymer (a), which may be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising:
[0090] - 15-99 wt% of a conjugated diene;
[0091] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0092] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0093] - 0-50 wt% of vinyl aromatic monomers; and
[0094] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0095] - 0 to 5 wt %, preferably 0 to 3 wt %, of ethylenically unsaturated monomers carrying ethylene oxide functions,
[0096] The weight percentages are based on the total monomers in the mixture of latex polymer a),
[0097] Combined or combined with:
[0098] (b) particles of latex polymer (b) obtainable by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising greater than 5 wt%, preferably at least 10 wt%, more preferably at least 15 wt%, of ethylenically unsaturated monomers having ethylene oxide functional groups, based on the total monomers in the latex polymer b) mixture.
[0099] A latex polymer (b) comprising at least one oxirane functional group
[0100] The latex polymer (b) used according to the present invention may be prepared by any suitable free radical emulsion polymerization process known in the art. Suitable process parameters are those discussed below with respect to the emulsion polymerization process for preparing latex polymer (a).
[0101] The unsaturated monomers used to prepare the latex polymer (b) and their relative amounts are not particularly critical, as long as the monomer mixture includes at least one ethylenically unsaturated monomer with ethylene oxide functionality. According to the present invention, the ethylene oxide functional ethylenically unsaturated monomer can be monofunctional ethylene oxide functionality and does not contain an oligomeric or polymeric backbone. In particular, the ethylene oxide functional ethylenically unsaturated monomer has a number average molecular weight of less than 280 Daltons.
[0102] Suitable ethylene oxide functional ethylenically unsaturated monomers may be selected from glycidyl (meth)acrylate, allyl glycidyl ether, vinyl glycidyl ether, vinyl cyclohexene oxide, limonene oxide, 2-ethyl glycidyl acrylate, 2-ethyl glycidyl methacrylate, 2-(n-propyl) glycidyl acrylate, 2-(n-propyl) glycidyl methacrylate, 2-(n-butyl) glycidyl acrylate, 2-(n-butyl) glycidyl methacrylate, glycidyl methyl methacrylate, glycidyl acrylate, (3',4'-epoxyheptyl)-2-ethyl acrylate, (3',4'-epoxyheptyl)-2-ethyl acrylate, 1-Epoxyheptyl)-2-ethyl methacrylate, (6',7'-epoxyheptyl)acrylate, (6',7'-epoxyheptyl)methacrylate, allyl-3,4-epoxyheptyl ether, 6,7-epoxyheptyl allyl ether, vinyl-3,4-epoxyheptyl ether, 3,4-epoxyheptyl vinyl ether, 6,7-epoxyheptyl vinyl ether, o-vinylbenzyl glycidyl ether, m-vinylbenzyl glycidyl ether, p-vinylbenzyl glycidyl ether, 3-vinyl epoxycyclohexane, α-methyl glycidyl methacrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and combinations thereof. Glycidyl (meth)acrylate is particularly preferred.
[0103] The ethylene oxide functional latex polymer (b) according to the present invention may include structural units derived from ethylenically unsaturated ethylene oxide functional monomers in an amount of 1-80 wt%, preferably 20-70 wt%, more preferably 25-65 wt%, and most preferably 35-65 wt%, based on the total weight of the monomers of the ethylene oxide functional latex particles (b). Therefore, the lower limit of the amount of ethylenically unsaturated ethylene oxide functional monomers may be 1 wt%, or 5 wt%, or 10 wt%, or 12 wt%, or 14 wt%, or 16 wt%, or 18 wt%, or 20 wt%, or 22 wt%, or 24 wt%, or 26 wt%, or 28 wt%, or 30 wt%, or 32 wt%, or 34 wt%, or 35 wt%, based on the total weight of the monomers of the ethylene oxide functional latex particles (b). Therefore, based on the total weight of the monomers of the ethylene oxide functional latex particles (b), the upper limit of the amount of ethylenically unsaturated ethylene oxide functional monomers can be 80wt%, or 75wt%, or 73wt%, or 70wt%, or 68wt%, or 65wt%, or 62wt%, or 60wt%, or 58wt%, or 56wt%, or 54wt%, or 52wt%, or 50wt%. It should be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is explicitly included in this specification.
[0104] Suitable additional monomers for preparing the ethylene oxide functional latex polymer (b) according to the present invention may be selected from:
[0105] - ethylenically unsaturated nitrile compounds;
[0106] - vinyl aromatic monomers;
[0107] - alkyl esters of ethylenically unsaturated acids;
[0108] - hydroxyalkyl esters of ethylenically unsaturated acids;
[0109] - amides of ethylenically unsaturated acids;
[0110] - ethylenically unsaturated acids;
[0111] - ethylenically unsaturated sulfonic acid monomers and / or ethylenically unsaturated phosphorus acid monomers
[0112] - vinyl carboxylates;
[0113] - conjugated dienes;
[0114] - a monomer having at least two ethylenically unsaturated groups; and
[0115] -A combination of these.
[0116] Examples of ethylenically unsaturated nitrile monomers that can be used to prepare the ethylene oxide functional latex polymer (b) according to the present invention include polymerizable unsaturated aliphatic nitrile monomers containing 2 to 4 carbon atoms in a linear or branched arrangement, which may be substituted with acetyl or another nitrile group. Such nitrile monomers include acrylonitrile, methacrylonitrile, α-cyanoethylacrylonitrile, fumaronitrile and combinations thereof, with acrylonitrile being most preferred.
[0117] Representatives of vinyl aromatic monomers include, for example, styrene, α-methylstyrene, p-methylstyrene, tert-butylstyrene and vinyltoluene. Preferably, the vinyl aromatic monomer is selected from the group consisting of styrene, α-methylstyrene and combinations thereof.
[0118] Esters of (meth)acrylic acid that can be used to prepare the ethylene oxide functional latex particles (b) according to the present invention include n-alkyl, isoalkyl or tert-alkyl esters of acrylic acid or (meth)acrylic acid, wherein the alkyl group has 1 to 20 carbon atoms; the reaction product of methacrylic acid with a glycidyl ester of a neo acid such as versatic acid, neodecanoic acid or pivalic acid; and hydroxyalkyl (meth)acrylate and alkoxyalkyl (meth)acrylate monomers.
[0119] Generally speaking, the preferred alkyl (meth)acrylates can be selected from C1-C 20 Alkyl esters, preferably (meth) acrylic acid C1-C 10Alkyl esters. Examples of such acrylate monomers include n-butyl acrylate, sec-butyl acrylate, methyl acrylate, ethyl acrylate, hexyl acrylate, tert-butyl acrylate, 2-ethyl-hexyl acrylate, isooctyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylbutyl acrylate, methyl methacrylate, butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, and hexadecyl methacrylate. Particularly preferred are esters of (meth)acrylic acid selected from methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and combinations thereof.
[0120] Hydroxyalkyl (meth)acrylate monomers that can be used to prepare the oxirane functional latex polymer (b) according to the present invention include hydroxyalkyl acrylate and hydroxyalkyl methacrylate monomers based on ethylene oxide, propylene oxide and higher alkylene oxides or mixtures thereof. Examples are hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxybutyl acrylate. Preferably, the hydroxyalkyl (meth)acrylate monomer is selected from 2-hydroxyethyl (meth)acrylate.
[0121] Amides of ethylenically unsaturated acids useful in preparing the ethylene oxide functional latex polymer (b) according to the present invention include acrylamide, methacrylamide and diacetone acrylamide. The preferred amide monomer is (meth)acrylamide.
[0122] Vinyl ester monomers that can be used to prepare the oxirane functional latex polymer (b) according to the present invention include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl benzoate, vinyl-2-ethylhexanoate, vinyl stearate and vinyl esters of versatic acid. The most preferred vinyl ester is vinyl acetate.
[0123] Ethylenically unsaturated carboxylic acid monomers suitable for preparing the ethylene oxide functional latex polymer (b) according to the present invention include monocarboxylic acid and dicarboxylic acid monomers and monoesters of dicarboxylic acids. In the practice of the present invention, it is preferred to use ethylenically unsaturated aliphatic monocarboxylic acids or dicarboxylic acids or anhydrides containing 3-5 carbon atoms. Examples of monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and examples of dicarboxylic acid monomers include fumaric acid, itaconic acid, maleic acid and maleic anhydride. Other suitable examples of ethylenically unsaturated acids include vinylacetic acid, vinyllactic acid, vinylsulfonic acid, 2-methyl-2-propylene-1-sulfonic acid, styrenesulfonic acid, acrylamidomethylpropanesulfonic acid and salts thereof. Preferably, the ethylenically unsaturated carboxylic acid monomer is selected from (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid and combinations thereof.
[0124] Conjugated diene monomers suitable for preparing the oxirane functional latex polymer (b) according to the present invention include conjugated diene monomers selected from the group consisting of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 1,3-octadiene, 2-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, 2,3-diethyl-1,3-butadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 3,7-dimethyl -1,3,6-octatriene, 2-methyl-6-methylene-1,7-octadiene, 7-methyl-3-methylene-1,6-octadiene, 1,3,7-octatriene, 2-ethyl-1,3-butadiene, 2-pentyl-1,3-butadiene, 3,7-dimethyl-1,3,7-octatriene, 3,7-dimethyl-1,3,6-octatriene, 3,7,11-trimethyl-1,3,6,10-dodecatetraene, 7,11-dimethyl-3-methylene-1,6,10-dodecatetriene, 2,6-dimethyl-2,4,6-octatriene, 2-phenyl-1,3-butadiene and 2-methyl-3-isopropyl-1,3-butadiene and 1,3-cyclohexadiene. 1,3-Butadiene, isoprene and combinations thereof are preferred conjugated dienes.
[0125] In addition, monomers having at least two ethylenically unsaturated groups can be used to prepare the ethylene oxide functional latex polymer (b). Suitable difunctional monomers (referred to herein as multifunctional monomers) capable of providing internal crosslinking and branching in the polymer can be selected from divinylbenzene and diacrylates and di(meth)acrylates. Examples are ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate and dipropylene glycol di(meth)acrylate. The monomer having at least two ethylenically unsaturated groups is preferably selected from divinylbenzene 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate and 1,6-hexanediol di(meth)acrylate.
[0126] The ethylene oxide functional latex polymer (b) according to the present invention may include structural units derived from:
[0127] - 0-50 wt%, preferably 0-30 wt%, more preferably 0-20 wt% of a monomer selected from ethylenically unsaturated nitrile compounds, preferably acrylonitrile;
[0128] - 0-95 wt %, preferably 0-70 wt %, more preferably 0-50 wt % of a vinyl aromatic monomer, preferably styrene;
[0129] - 0-95 wt%, preferably 5-95 wt%, more preferably 20-95 wt% of C1-C8 alkyl (meth)acrylate;
[0130] - 0-10 wt%, preferably 0-7 wt%, more preferably 0.01-7 wt% of ethylenically unsaturated acid, preferably (meth)acrylic acid;
[0131] - 0-10 wt%, preferably 0-8 wt%, more preferably 0-6 wt% of ethylenically unsaturated compounds having silane groups, sulfonate groups, sulfonic acid groups, phosphate groups, amide groups and / or N-methylolamide groups;
[0132] - 0-50 wt%, preferably 0-40 wt%, more preferably 0-20 wt% of vinyl carboxylate, preferably vinyl acetate;
[0133] 1-80 wt%, preferably 20-70 wt%, more preferably 25-65 wt%, most preferably 35-65 wt% of structural units derived from ethylenically unsaturated oxirane-functional monomers.
[0134] Alternatively, the ethylene oxide functional latex polymer (b) according to the present invention may include structural units derived from:
[0135] - 2-95 wt%, preferably 10-95 wt%, more preferably 20-95 wt% of a conjugated diene, preferably selected from butadiene, isoprene and a combination thereof, more preferably butadiene;
[0136] -1-50wt%, preferably 5-50wt%, more preferably 5-40wt% of a monomer selected from ethylenically unsaturated nitrile compounds, preferably acrylonitrile;
[0137] - 0-95 wt %, preferably 0-90 wt %, more preferably 0-70 wt % of a vinyl aromatic monomer, preferably styrene;
[0138] - 0-95 wt%, preferably 0-90 wt%, more preferably 0-70 wt% of C1-C8 alkyl (meth)acrylate;
[0139] - 0-10 wt%, preferably 0-8 wt%, more preferably 0-7 wt% of ethylenically unsaturated acid, preferably (meth)acrylic acid;
[0140] - 0-10 wt%, preferably 0-8 wt%, more preferably 0-6 wt% of ethylenically unsaturated compounds having silane groups, sulfonate groups, sulfonic acid groups, phosphate groups, amide groups and / or N-methylolamide groups;
[0141] 1-80 wt%, preferably 20-70 wt%, more preferably 25-65 wt%, most preferably 35-65 wt% of structural units derived from ethylenically unsaturated oxirane-functional monomers.
[0142] According to the present invention, the amount of monomers defined above used for preparing the latex polymer (b) may total up to 100 wt%.
[0143] The glass transition temperature (midpoint temperature Tmg) of the ethylene oxide functional latex polymer (b) according to the present invention (determined by DSC according to ASTM D3418-03) can be -50° to 50°C, preferably -40° to 40°C, more preferably -30° to 30°C, more preferably -25° to 25°C and most preferably -22° to 22°C. Thus, the lower limit of the Tmg range can be -50, -45, -40, -38, -36, -34, -32, -30, -29, -28, -27, -26, -25, -24, -23 or -22°C. The upper limit of the Tmg range can be 50, 45, 40, 38, 36, 34, 32, 30, 29, 28, 27, 26, 25, 24, 23 or 22°C. It will be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is expressly encompassed in this specification.
[0144] The oxirane functional latex particles (b) according to the present invention, whether used as a latex added during the polymerization of the latex polymer (a) or as a preformed latex blended with the latex polymer (a), preferably have a z-average particle size of 5-90 nm, more preferably 15-85 nm, more preferably 20-80 nm, as measured by Malvern zetasizer nano S (ZEN 1600) using dynamic light scattering (DLS). Thus, the lower limit of the z-average particle size may be 5 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm or 20 nm, while the upper limit may be 90 nm, 85 nm, 80 nm, 75 nm, 70 nm, 65 nm, 60 nm, 55 nm, 50 nm, 45 nm, 40 nm, 38 nm, 36 nm, 34 nm, 32 nm or 30 nm. It will be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is expressly encompassed in this specification.
[0145] It will be appreciated by those skilled in the art that the ethylene oxide functional latex polymer (b) of the present invention can be used as particles present in the emulsion polymerization of the latex polymer (a) (e.g., as seed particles), or can be blended with a preformed latex polymer (a), wherein the preformed latex polymer (a) can be prepared by emulsion polymerization with or without the ethylene oxide functional latex polymer (b) according to the present invention as particles present in the emulsion polymerization, such as as seed particles. It will also be appreciated by those skilled in the art that the ethylene oxide functional latex particles (b) used as particles present in the emulsion polymerization of the preformed latex polymer (a) and the ethylene oxide functional latex polymer (b) blended with the preformed latex polymer (a) can be the same or different.
[0146] Latex polymer (a)
[0147] According to the present invention, the ethylenically unsaturated monomer mixture used to prepare the latex polymer (a) comprises:
[0148] - 15-99 wt% of a conjugated diene;
[0149] -1 to 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds;
[0150] - 0.05-10 wt% of ethylenically unsaturated carboxylic acid and / or its salt;
[0151] - 0-50 wt% of vinyl aromatic monomers; and
[0152] - 0 to 65% by weight of alkyl esters of ethylenically unsaturated acids,
[0153] The weight percentages are based on the total monomers used in the emulsion polymerization.
[0154] In the ethylenically unsaturated monomer mixture, there may be present further ethylenically unsaturated monomers selected from:
[0155] - hydroxyalkyl esters of ethylenically unsaturated acids;
[0156] - amides of ethylenically unsaturated acids;
[0157] - vinyl carboxylates;
[0158] - monomers having at least two ethylenically unsaturated groups;
[0159] - ethylenically unsaturated silanes;
[0160] - ethylene oxide-functional ethylenically unsaturated compounds; and
[0161] -A combination of these.
[0162] According to the present invention, the ethylenically unsaturated monomer mixture used to prepare the latex polymer (a) may be free of ethylene oxide functional monomers.
[0163] The conjugated diene monomers suitable for preparing the latex polymer (a) according to the present invention include conjugated diene monomers selected from the group consisting of 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 2,4-hexadiene, 1,3-octadiene, 2-methyl-1,3-pentadiene, 2,3-dimethyl-1,3-pentadiene, 3,4-dimethyl-1,3-hexadiene, 2,3-diethyl-1,3-butadiene, 4,5-diethyl-1,3-octadiene, 3-butyl-1,3-octadiene, 3,7-dimethyl-1,3,6-octatri ... 6-methylene-1,7-octadiene, 7-methyl-3-methylene-1,6-octadiene, 1,3,7-octatriene, 2-ethyl-1,3-butadiene, 2-pentyl-1,3-butadiene, 3,7-dimethyl-1,3,7-octatriene, 3,7-dimethyl-1,3,6-octatriene, 3,7,11-trimethyl-1,3,6,10-dodecatetraene, 7,11-dimethyl-3-methylene-1,6,10-dodecatetriene, 2,6-dimethyl-2,4,6-octatriene, 2-phenyl-1,3-butadiene and 2-methyl-3-isopropyl-1,3-butadiene, 1,3-cyclohexadiene, laurylene, ocimene and farnasene. 1,3-Butadiene, isoprene and combinations thereof are preferred conjugated dienes. 1,3-Butadiene is the most preferred diene. Typically, the amount of conjugated diene monomer ranges from 15-99 wt%, preferably 20-99 wt%, more preferably 30-75 wt%, and most preferably 40-70 wt%, based on the total weight of the monomers. Thus, the conjugated diene may be present in an amount of at least 15 wt%, at least 20 wt%, at least 22 wt%, at least 24 wt%, at least 26 wt%, at least 28 wt%, at least 30 wt%, at least 32 wt%, at least 34 wt%, at least 36 wt%, at least 38 wt%, or at least 40 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0164] Therefore, the conjugated diene monomer can be no more than 95wt%, no more than 90wt%, no more than 85wt%, no more than 80wt%, no more than 78wt%, no more than 76wt%, no more than 74wt%, no more than 72wt%, no more than 70wt%, no more than 68wt%, no more than 66wt%, no more than 64wt%, no more than 62wt%, no more than 60wt%, no more than 58wt% or no more than 56wt% of the amount used. Those skilled in the art will appreciate that any range between any explicitly disclosed lower and upper limits is the disclosure of this article.
[0165] Unsaturated nitrile monomers that can be used to prepare latex polymer (a) particles include polymerizable unsaturated aliphatic nitrile monomers containing 2 to 4 carbon atoms in a linear or branched arrangement, which may be substituted with acetyl or another nitrile group. Such nitrile monomers include acrylonitrile, methacrylonitrile, α-cyanoethylacrylonitrile, butenedinitrile and combinations thereof, with acrylonitrile being the most preferred. These nitrile monomers may be included in an amount of 1 to 80 wt%, preferably 10 to 70 wt%, or 1 to 60 wt%, and more preferably 15 to 50 wt%, even more preferably 20 to 50 wt%, and most preferably 23 to 43 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0166] Thus, the unsaturated nitrile can be present in an amount of at least 1 wt%, 5 wt%, at least 10 wt%, at least 12 wt%, at least 14 wt%, at least 16 wt%, at least 18 wt%, at least 20 wt%, at least 22 wt%, at least 24 wt%, at least 26 wt%, at least 28 wt%, at least 30 wt%, at least 32 wt%, at least 34 wt%, at least 36 wt%, at least 38 wt% or at least 40 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0167] Therefore, the unsaturated nitrile monomer can be no more than 80wt%, no more than 75wt%, no more than 73wt%, no more than 70wt%, no more than 68wt%, no more than 66wt%, no more than 64wt%, no more than 62wt%, no more than 60wt%, no more than 58wt%, no more than 56wt%, no more than 54wt%, no more than 52wt%, no more than 50wt%, no more than 48wt%, no more than 46wt% or no more than 44wt% amount use. Those skilled in the art will appreciate that any scope between any clearly disclosed lower limit and the upper limit is the disclosure of this paper.
[0168] The ethylenically unsaturated carboxylic acid or its salt can be selected from monocarboxylic acid and dicarboxylic acid monomers and their anhydrides and partial esters of polycarboxylic acids. In the practice of the present invention, it is preferred to use ethylenically unsaturated aliphatic monocarboxylic acids or dicarboxylic acids or anhydrides containing 3 to 5 carbon atoms. Examples of monocarboxylic acid monomers include acrylic acid, methacrylic acid, crotonic acid, and examples of dicarboxylic acid monomers include fumaric acid, itaconic acid, maleic acid, cis-cyclohexene-1,2-dicarboxylic acid, dimethylmaleic acid, bromomaleic acid, 2,3-dichloromaleic acid and (2-dodecene-1-yl)succinic acid. The example of polycarboxylic acid partial ester comprises maleic acid monomethyl ester, fumaric acid monomethyl ester, maleic acid monoethyl ester, fumaric acid monoethyl ester, maleic acid monopropyl ester, fumaric acid monopropyl ester, maleic acid monobutyl ester, fumaric acid monobutyl ester, maleic acid list (2-ethylhexyl) ester, fumaric acid list (2-ethylhexyl) ester.The example of other applicable ethylenically unsaturated acids comprises vinylacetic acid, vinyl lactic acid, vinyl sulfonic acid, 2-methyl-2-propylene-1-sulfonic acid, styrene sulfonic acid, acrylamidomethylpropane sulfonic acid and salt thereof.(methyl) acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid and combination thereof are particularly preferred.
[0169] The use of ethylenically unsaturated carboxylic acid monomers affects the properties of the polymer dispersion and the film formed therefrom. The type and amount of these monomers are determined accordingly. Typically, this amount is 0.05-10 wt%, particularly 0.1-10 wt% or 0.05-7 wt%, preferably 0.1-9 wt%, more preferably 0.1-8 wt%, even more preferably 1-7 wt%, and most preferably 2-7 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a). Thus, the ethylenically unsaturated carboxylic acid monomers may be present in an amount of at least 0.01 wt%, at least 0.05 wt%, at least 0.1 wt%, at least 0.3 wt%, at least 0.5 wt%, at least 0.7 wt%, at least 0.9 wt%, at least 1 wt%, at least 1.2 wt%, at least 1.4 wt%, at least 1.6 wt%, at least 1.8 wt%, at least 2 wt%, at least 2.5 wt%, or at least 3 wt%. Likewise, the ethylenically unsaturated carboxylic acid monomer may be present in an amount of no more than 10 wt%, no more than 9.5 wt%, no more than 9 wt%, no more than 8.5 wt%, no more than 8 wt%, no more than 7.5 wt%, no more than 7 wt%, no more than 6.5 wt%, no more than 6 wt%, no more than 5.5 wt%, or no more than 5 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a). It will be understood by those skilled in the art that any range defined by an explicitly disclosed lower limit and an explicitly disclosed upper limit is intended to be included in the disclosure herein.
[0170] Representatives of vinyl aromatic monomers include, for example, styrene, α-methylstyrene, vinyltoluene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, 2,4-diisopropylstyrene, 2,4-dimethylstyrene, 4-tert-butylstyrene, 5-tert-butyl-2-methylstyrene, 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, 4-bromostyrene, 2-methyl-4,6-dichlorostyrene, 2,4-dibromostyrene, vinylnaphthalene, vinyltoluene and vinylxylene, 2-vinylpyridine, 4-vinylpyridine and 1,1-diphenylethylene and substituted 1,1-diphenylethylene, 1,2-diphenylethylene and substituted 1,2-diphenylethylene. Mixtures of one or more vinyl aromatic compounds may also be used. Preferred monomers are styrene and α-methylstyrene. The vinyl aromatic compound may be used in the range of 0-50 wt%, preferably 0-40 wt%, more preferably 0-25 wt%, even more preferably 0-15 wt%, and most preferably 0-10 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a). Thus, the vinyl aromatic compound may be present in an amount of no more than 35 wt%, no more than 30 wt%, no more than 25 wt%, no more than 20 wt%, no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a). The vinyl aromatic compound may also be completely absent.
[0171] Additionally, the mixture of ethylenically unsaturated monomers of the latex polymer (a) according to the invention may comprise further ethylenically unsaturated monomers different from the monomers defined above. These monomers may be selected from esters of (meth)acrylic acid, vinyl esters and amides of ethylenically unsaturated acids or ethylenically unsaturated silane compounds.
[0172] Vinyl ester monomers that can be used according to the present invention include vinyl acetate, vinyl propionate, vinyl butyrate, vinyl benzoate, vinyl-2-ethylhexanoate, vinyl stearate, and vinyl versatate. The most preferred vinyl ester monomer for use in the present invention is vinyl acetate. Typically, the vinyl ester monomer may be present in an amount of no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0173] Examples of suitable ethylenically unsaturated silane compounds can be selected from triethoxyvinylsilane and 3-methacryloxypropyltrimethoxysilane. The ethylenically unsaturated silane compound can be present in an amount of 0.05-5.0 wt%, preferably 0.3-2.0 wt%, more preferably 0.3-1.0 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0174] Esters of (meth)acrylic acid that can be used according to the present invention include acrylic acid or n-alkyl, isoalkyl or tert-alkyl (meth)acrylates, wherein the alkyl group has 1 to 20 carbon atoms; reaction products of methacrylic acid with glycidyl esters of neo acids such as versatic acid, neodecanoic acid or pivalic acid; and hydroxyalkyl (meth)acrylate and alkoxyalkyl (meth)acrylate monomers.
[0175] In general, the preferred alkyl esters of (meth)acrylic acid can be selected from C1-C 10 Alkyl esters, preferably C1-C8 alkyl (meth)acrylates. Examples of such acrylate monomers include n-butyl acrylate, sec-butyl acrylate, ethyl acrylate, hexyl acrylate, tert-butyl acrylate, 2-ethyl-hexyl acrylate, isooctyl acrylate, 4-methyl-2-pentyl acrylate, 2-methylbutyl acrylate, methyl methacrylate, butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, ethyl methacrylate, isopropyl methacrylate, hexyl methacrylate, cyclohexyl methacrylate, and hexadecyl methacrylate. Methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and combinations thereof are preferred.
[0176] Typically, the alkyl (meth)acrylate monomer may be present in an amount of no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt% or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0177] Hydroxyalkyl (meth)acrylate monomers that can be used to prepare the polymer latex according to the present invention include hydroxyalkyl acrylate and hydroxyalkyl methacrylate monomers based on ethylene oxide, propylene oxide and higher carbon alkylene oxides or mixtures thereof. Examples are hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and hydroxybutyl acrylate. Preferably, the hydroxyalkyl (meth)acrylate monomer is 2-hydroxyethyl (meth)acrylate. Typically, the hydroxyalkyl (meth)acrylate monomer may be present in an amount of no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt% or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0178] The (meth) alkoxyalkyl acrylate monomers that can be used in the present invention include methoxyethyl methacrylate, ethoxyethyl methacrylate, methoxyethyl methacrylate, ethoxyethyl acrylate, butoxyethyl methacrylate, methoxybutyl acrylate, and methoxyethoxyethyl acrylate. Preferred (meth) alkoxyalkyl acrylate monomers are ethoxyethyl acrylate and methoxyethyl acrylate. Typically, the amount of the (meth) alkoxyethyl alkyl acrylate monomer may be no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0179] The amides of ethylenically unsaturated acids that can be used to prepare the polymer latex according to the present invention include acrylamide, methacrylamide and diacetone acrylamide. The preferred amide monomer is (meth) acrylamide. In order to introduce functional groups that can self-crosslink during heat treatment into the polymer particles of the present invention, monomers including N-hydroxymethylamide groups can be used. Suitable monomers are N-hydroxymethyl (meth) acrylamide, N-methoxymethyl-(meth) acrylamide, N-n-butoxy-methyl-(meth) acrylamide, N-isobutoxy-methyl-(meth) acrylamide, N-acetoxymethyl-(meth) acrylamide, N (-2,2-dimethoxy-1-hydroxyethyl) acrylamide. Typically, the amides of ethylenically unsaturated acids may be present in an amount of no more than 18 wt%, no more than 16 wt%, no more than 14 wt%, no more than 12 wt%, no more than 10 wt%, no more than 8 wt%, no more than 6 wt%, no more than 4 wt%, no more than 2 wt% or no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers of the latex polymer (a).
[0180] In addition, monomers having at least two ethylenically unsaturated groups may be present in the monomer mixture used to prepare the polymer latex of the present invention in an amount of 0-6.0 wt%, preferably 0.1-3.5 wt%, based on the total weight of the ethylenically unsaturated monomers. Typically, these monomers may be present in an amount of no more than 6 wt%, no more than 4 wt%, no more than 2 wt%, no more than 1 wt%, based on the total weight of the ethylenically unsaturated monomers. Suitable difunctional monomers (referred to herein as multifunctional monomers) capable of providing internal crosslinking and branching in the polymer may be selected from divinylbenzene and diacrylates and di(meth)acrylates. Examples are ethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, tripropylene glycol di(meth)acrylate, butanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and dipropylene glycol di(meth)acrylate. The monomer having at least two ethylenically unsaturated groups is preferably selected from divinylbenzene, 1,2-ethylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate and trimethylolpropane tri(meth)acrylate.
[0181] Suitable oxirane functional monomers for preparing latex polymer (a) are the oxirane functional monomers described above including the preferred embodiment oxirane functional latex polymer (b). If used, the oxirane functional monomer is preferably present in an amount of up to 5 wt%, more preferably up to 3 wt%, based on the total amount of monomers used to prepare latex polymer (a). However, as mentioned above, it is most preferred that latex polymer (a) does not contain oxirane functional groups.
[0182] The mixture of ethylenically unsaturated monomers used in the latex polymer (a) may include:
[0183] - 20-99 wt% of a conjugated diene, preferably selected from butadiene, isoprene and a combination thereof, more preferably butadiene;
[0184] -1-60 wt% of a monomer selected from ethylenically unsaturated nitrile compounds, preferably acrylonitrile;
[0185] - 0-40 wt% of a vinyl aromatic monomer, preferably styrene;
[0186] - 0-25 wt% of C1-C8 alkyl (meth)acrylate;
[0187] - 0.05-7 wt % of ethylenically unsaturated acid, preferably (meth)acrylic acid;
[0188] -0-10 wt% of vinyl ester:
[0189] - 0 to 10 wt % of ethylenically unsaturated compounds carrying silane, amide and / or N-methylolamide groups,
[0190] Weight percentages are based on the total monomers present in the mixture.
[0191] According to the present invention, the monomers defined above for preparing the latex polymer (a) may be added in an amount of up to 100 wt%.
[0192] According to the invention, the mixture of ethylenically unsaturated monomers to be polymerized in the free-radical emulsion polymerization may also comprise:
[0193] (a) 15 to 90 wt % of isoprene;
[0194] (b) 1-80 wt % of acrylonitrile;
[0195] (c) 0.01 to 10 wt %, preferably 0.05 to 10 wt %, of at least one ethylenically unsaturated acid;
[0196] (d) 0 to 40 wt% of at least one aromatic vinyl compound, and
[0197] (e) 0-20 wt% of at least one other ethylenically unsaturated compound different from any one of compounds (a)-(d). The range of components (a) and / or (b) can be selected from the ranges of (a) conjugated dienes and (b) unsaturated nitriles as disclosed above. Similarly, specific embodiments and amounts of components (c), (d) and / or (e) can be selected from those described above for components (c), (d) and additional polymers.
[0198] The z average particle size of the latex particles (a) according to the present invention measured by dynamic light scattering (DLS) using a Malvern zetasizer nano S (ZEN 1600) is preferably 70-1000 nm, more preferably 80-1000 nm, more preferably 90-1000 nm, 100-1000 nm, more preferably 110-600 nm, more preferably 120-500 nm. Therefore, the lower limit of the z average particle size of the latex particles (a) may be 70 nm, 80 nm, 90 nm, 100 nm, 105 nm, 110 nm or 120 nm; the upper limit of the z average particle size may be 900 nm, 800 nm, 700 nm, 600 nm, 500 nm, 400 nm, 350 nm, 300 nm, 270 nm, 250 nm, 230 nm, 210 nm or 200 nm. It will be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is expressly encompassed in this specification.
[0199] According to the present invention, it is particularly preferred that the z-average particle size of latex polymer (a) is larger than the z-average particle size of latex polymer (b).
[0200] The preparation method of the polymer latex of the present invention:
[0201] The latex polymer (a) according to the invention can be prepared by any emulsion polymerization process known to the person skilled in the art, provided that a monomer mixture as defined herein is employed. Particularly suitable is the process described in EP-A 792 891.
[0202] In the emulsion polymerization for preparing the latex polymer (a) of the present invention, a seed latex may be used. Preferably, the seed latex is a latex polymer (b) as described above, including all disclosed variations. Alternatively, any other seed particles known to those skilled in the art may be used. However, if latex polymer (b) is not used as a seed particle, the particles of latex polymer (b) will have to be incorporated into the polymer latex of the present invention in any other suitable manner, such as mixing a preformed latex including particles of latex polymer (a) with a preformed latex including particles of latex polymer (b).
[0203] The seed latex particles are preferably present in an amount of 0.01-10, preferably 1-5, parts by weight, based on 100 parts by weight of the total ethylenically unsaturated monomers used in the polymer latex (including the monomers used to prepare the seed particles, such as the ethylene oxide functional latex particles (b)). Thus, the lower limit of the amount of seed latex particles may be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4 or 2.5 parts by weight. The upper limit of the amount can be 10, 9, 8, 7, 6, 5.5, 5, 4.5, 4, 3.8, 3.6, 3.4, 3.3, 3.2, 3.1 or 3 parts by weight. It should be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is explicitly included in this specification.
[0204] The process for preparing the above-mentioned polymer latex can be carried out at a temperature of 0-130° C., preferably 0-100° C., particularly preferably 5-70° C., very particularly preferably 5-60° C., in the absence of one or more emulsifiers, one or more colloids and one or more initiators. The temperature includes all values and subvalues therebetween, especially including 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120 and 125° C.
[0205] Initiators that can be used in the practice of the present invention include water-soluble and / or oil-soluble initiators that are effective for polymerization purposes. Representative initiators are well known in the art and include, for example, azo compounds (such as AIBN, AMBN, and cyanovaleric acid) and inorganic peroxy compounds such as hydrogen peroxide, sodium peroxodisulfate, potassium peroxodisulfate, ammonium peroxodisulfate, sodium percarbonate, potassium percarbonate, ammonium percarbonate, sodium peroxyborate, potassium peroxyborate, and ammonium peroxyborate; and organic peroxy compounds such as alkyl hydroperoxides, dialkyl peroxides, acyl hydroperoxides, and diacyl peroxides; and esters such as tert-butyl perbenzoate; and combinations of inorganic and organic initiators.
[0206] The initiator is used in an amount sufficient to initiate the polymerization reaction at the desired rate. Generally speaking, an initiator amount of 0.01-5 wt%, preferably 0.1-4 wt%, based on the weight of the total polymer is sufficient. The amount of initiator is most preferably 0.01-2 wt%, based on the total weight of the polymer. The amount of initiator includes all values and subvalues therebetween, especially including 0.01, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 4 and 4.5 wt%, based on the total weight of the polymer.
[0207] As is well known in the art, the above-mentioned inorganic and organic peroxy compounds may also be used alone or in combination with one or more suitable reducing agents. Examples of such reducing agents which may be mentioned are sulfur dioxide, alkali metal bisulfites, alkali metal and ammonium bisulfites, thiosulfates, dithionites and formaldehyde sulfoxylates, as well as hydroxylamine hydrochloride, hydrazine sulfate, iron(II) sulfate, cuprous naphthenate, glucose, sulfonic acid compounds (such as sodium methanesulfonate), amine compounds (such as dimethylaniline) and ascorbic acid. More preferably, sodium salts of proprietary organic sulfinic acid derivatives, such as FF6 or FF6M. The amount of the reducing agent is preferably 0.03-10 parts by weight per part by weight of the polymerization initiator.
[0208] Surfactants or emulsifiers suitable for stabilizing latex particles include conventional surfactants of polymerization processes. One or more surfactants can be added to the aqueous phase and / or the monomer phase. The effective amount of surfactant in the seed method is selected to support the particles to be colloidal and stable, minimize contact between particles and prevent coagulation. In non-seed methods, the effective amount of surfactant is selected to affect the particle size.
[0209] Representative surfactants include saturated and ethylenically unsaturated sulfonic acids or their salts, including, for example, unsaturated hydrocarbon sulfonic acids, such as vinyl sulfonic acid, allyl sulfonic acid and methallyl sulfonic acid and their salts; aromatic hydrocarbon acids, such as p-styrene sulfonic acid, isopropenylbenzenesulfonic acid and vinyloxybenzenesulfonic acid and their salts; sulfoalkyl esters of acrylic acid and methacrylic acid, such as sulfoethyl methacrylate and sulfopropyl methacrylate and their salts, and 2-acrylamido-2-methylpropanesulfonic acid and its salts; oxidized alkylated diphenyl disulfonates, dihexyl esters of sodium dodecylbenzenesulfonate and sodium sulfosuccinate, sodium alkyl esters of sulfonic acids, ethoxylated alkylphenols and ethoxylated alcohols; fatty alcohol (poly) ether sulfates.
[0210] The type and amount of surfactant are usually determined by the number of particles, its particle size and its composition. Usually, based on the total weight of monomer, the surfactant is used in an amount of 0-20wt%, preferably 0-10wt%, more preferably 0-5wt%. The amount of surfactant includes all values and subvalues between, especially including 0,0.1,0.5,1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18 and 19wt% based on the total weight of monomer. According to one embodiment of the present invention, the polymerization reaction is carried out without using a surfactant.
[0211] Various protective colloids can also be used to replace the above-mentioned surfactant or to add in addition. Suitable colloids include polyols, such as partially acetylated polyvinyl alcohol, casein, hydroxyethyl starch, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polysaccharides and degraded polysaccharides, polyethylene glycol and gum arabic. Preferred protective colloids are carboxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose. Generally speaking, these protective colloids are used in a content of 0-10 weight parts, preferably 0-5 weight parts, more preferably 0-2 weight parts, based on the total weight of monomers. The amount of the protective colloid includes all values and subvalues between, particularly including 1,2,3,4,5,6,7,8 and 9wt% based on the total weight of monomers.
[0212] It will be appreciated by those skilled in the art that the types and amounts of monomers with polar functional groups, surfactants and protective colloids are selected to make the polymer latex according to the present invention suitable for dip molding applications. Therefore, it is preferred that the polymer latex composition of the present invention has a certain maximum electrolyte stability, which is determined as a critical coagulation concentration of less than 30 mmol / l CaCl2, preferably less than 25 mmol / l, more preferably less than 20 mmol / l, and most preferably less than 10 mmol / l (measured at pH 10 and 23°C, with a total solid content of the composition of 0.1%).
[0213] If the electrolyte stability is too high, it is difficult to coagulate the polymer latex in the dipping process, with the result that a continuous film of the polymer latex cannot be formed on the dipped mold or the thickness of the resulting product is uneven.
[0214] It is within the routine of those skilled in the art to appropriately adjust the electrolyte stability of the polymer latex. The electrolyte stability will depend on certain different factors, such as the amount and selection of monomers, particularly monomers containing polar functional groups, used to prepare the polymer latex, and the selection and amount of the stabilizing system, such as the emulsion polymerization process used to prepare the polymer latex. The stabilizing system may contain a surfactant and / or a protective colloid.
[0215] A person skilled in the art can adjust the stabilizing system according to the monomers selected for preparing the polymer latex of the present invention and their relative amounts so as to achieve the electrolyte stability according to the present invention.
[0216] Because there are so many different factors affecting electrolyte stability, it is most preferred to adjust by trial and error experimentation. However, this experimentation can be easily performed without much effort using the test methods disclosed above for electrolyte stability.
[0217] It is generally advisable to carry out the emulsion polymerization in the additional presence of buffer substances and chelating agents. Suitable substances are, for example, alkali metal carbonates and bicarbonates, alkali metal phosphates and pyrophosphates (buffer substances) and alkali metal salts of ethylenediaminetetraacetic acid (EDTA) or hydroxy-2-ethylenediaminetetraacetic acid (HEEDTA) as chelating agents. The amount of buffer substances and chelating agents is generally 0.001 to 1.0% by weight, based on the total amount of monomers.
[0218] In addition, it is advantageous to use chain transfer agents (regulators) in the emulsion polymerization. Typical agents are, for example, organic sulfur compounds such as thioesters, 2-mercaptoethanol, 3-mercaptopropionic acid and C1-C 12 Alkyl mercaptans, n-dodecyl mercaptan and tert-dodecyl mercaptan are preferred. The amount of chain transfer agent (if present) is generally 0.05-3.0 wt%, preferably 0.2-2.0 wt%, based on the total weight of monomers used.
[0219] Furthermore, it may be beneficial to introduce partial neutralization during the polymerization process. It will be appreciated by those skilled in the art that by appropriate selection of this parameter, the necessary control can be achieved.
[0220] In order to prepare the latex composition of the present invention, various other additives and ingredients can be added. Such additives include, for example, defoamers, wetting agents, thickeners, plasticizers, fillers, pigments, dispersants, optical brighteners, antioxidants, biocides and metal chelators. Known defoamers include silicone oils and acetylene glycols. Commonly used known wetting agents include alkylphenol ethoxylates, alkali metal dialkyl sulfosuccinates, acetylene glycols and alkali metal alkyl sulfates. Typical thickeners include polyacrylates, polyacrylamides, xanthan gum, modified cellulose or particulate thickeners such as silica and clay. Typical plasticizers include mineral oils, liquid polybutene, liquid polyacrylates and lanolin. Titanium dioxide (TiO2), calcium carbonate and clay are commonly used fillers.
[0221] In an alternative embodiment of the present invention, a polymer latex comprising particles of latex polymer (a) and a polymer latex comprising particles of latex polymer (b) are preformed, and the two latexes are subsequently combined. The emulsion polymerization used to prepare the preformed latexes comprising latex polymer (a) and latex polymer (b), respectively, can be carried out in the same manner as described above for preparing a latex comprising latex polymer (a) (including all variations disclosed).
[0222] The polymer latex of the present invention may include 50-99 wt%, preferably 60-98 wt%, more preferably 65-97 wt%, most preferably 70-96 wt% of latex polymer (a) particles based on the total weight of latex particles in the composition and 1-50 wt%, preferably 2-40 wt%, more preferably 3-35 wt%, most preferably 4-30 wt% of ethylene oxide functional latex polymer (b) based on the total weight of latex particles in the composition. Therefore, the lower limit of the amount of latex polymer (a) particles based on the total weight of latex particles in the composition may be 50 wt%, or 55 wt%, or 58 wt%, or 60 wt%, or 62 wt%, or 63 wt%, or 64 wt%, or 65 wt%, or 66 wt%, or 67 wt%, or 68 wt%, or 69 wt%, or 70 wt%. The upper limit of the amount of the latex polymer (a) particles may be 99 wt%, or 98 wt%, or 97 wt%, or 96 wt%, or 95 wt%, or 94 wt%, or 93 wt%, or 92 wt%, or 91 wt%, or 90 wt%, or 89 wt%, or 88 wt%, or 87 wt%, or 86 wt%, or 85 wt%, or 84 wt%, or 83 wt%, or 82 wt%, or 81 wt%, or 80 wt%, based on the total weight of the latex particles in the composition. The lower limit of the amount of the latex polymer (b) particles may be 1 wt%, or 1 wt%, or 1 wt%, or 1 wt%, or 5 wt%, or 6 wt%, or 7 wt%, or 8 wt%, or 9 wt%, or 10 wt%, or 11 wt%, or 12 wt%, or 13 wt%, or 14 wt%, or 15 wt%, or 16 wt%, or 17 wt%, or 18 wt%, or 19 wt%, or 20 wt%, based on the total weight of the latex particles in the composition. The upper limit of the amount of latex polymer (b) particles can be 50wt%, or 45wt%, or 42wt%, or 40wt%, or 38wt%, or 37wt%, or 36wt%, or 35wt%, or 34wt%, or 33wt%, or 32wt%, or 31wt%, or 30wt%, based on the total weight of latex particles in the composition. It should be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is explicitly included in this specification.
[0223] To prepare the polymer latex of the present invention, the ethylenically unsaturated monomer mixture of latex polymer (a) can also be polymerized in the presence of ethylene oxide functional latex polymer (b) particles in a free radical emulsion polymerization to form a first polymer latex (e.g., the ethylene oxide functional latex polymer (b) particles can be present as seed particles) to form a first polymer latex, and a second polymer latex including latex polymer (b) particles is preformed, and the two latexes are subsequently combined, wherein the ethylene oxide functional latex polymer (b) present in the polymerization reaction of latex polymer (a) and in the second polymer latex including latex polymer (b) particles can be the same or different. The respective emulsion polymerizations to form the first and second latexes can be carried out in the same manner as described above for preparing a latex including latex polymer (a) (including all variations disclosed).
[0224] In the case described, the polymer latex of the present invention may include 50-99 wt %, preferably 60-98 wt %, more preferably 65-97 wt %, and most preferably 70-96 wt % of latex polymer (a) particles, based on the total weight of latex particles in the composition, wherein the latex polymer (a) is prepared in the presence of 0.01-10, preferably 1-5 parts by weight of ethylene oxide functional latex polymer (b) particles based on 100 parts by weight of total ethylenically unsaturated monomers in the polymer latex (a) (including ethylenically unsaturated monomers present in the polymerization reaction of latex polymer (a) to prepare ethylene oxide functional latex polymer (b)), and 1-50 wt %, preferably 2-40 wt %, more preferably 3-35 wt %, and most preferably 4-30 wt % of second ethylene oxide functional latex particles (b), based on the total weight of latex particles in the composition.
[0225] Thus, the lower limit of the amount of ethylene oxide functional latex polymer (b) used to prepare the first latex can be 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, or 2.5 parts by weight. The upper limit of the amount can be 10, 9, 8, 7, 6, 5.5, 5, 4.5, 4, 3.8, 3.6, 3.4, 3.3, 3.2, 3.1, or 3 parts by weight. It will be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is expressly contemplated in this specification.
[0226] Therefore, the lower limit of the amount of the latex polymer (a) particles may be 50 wt%, or 55 wt%, or 58 wt%, or 60 wt%, or 62 wt%, or 63 wt%, or 64 wt%, or 65 wt%, or 66 wt%, or 67 wt%, or 68 wt%, or 69 wt%, or 70 wt%, based on the total weight of the latex particles in the composition. The upper limit of the amount of the latex polymer (a) particles may be 99 wt%, or 98 wt%, or 97 wt%, or 96 wt%, or 95 wt%, or 94 wt%, or 93 wt%, or 92 wt%, or 91 wt%, or 90 wt%, or 89 wt%, or 88 wt%, or 87 wt%, or 86 wt%, or 85 wt%, or 84 wt%, or 83 wt%, or 82 wt%, or 81 wt%, or 80 wt%, based on the total weight of the latex particles in the composition. The lower limit of the amount of the second latex polymer (b) particles can be 1 wt%, or 1 wt%, or 1 wt%, or 1 wt%, or 5 wt%, or 6 wt%, or 7 wt%, or 8 wt%, or 9 wt%, or 10 wt%, or 11 wt%, or 12 wt%, or 13 wt%, or 14 wt%, or 15 wt%, or 16 wt%, or 17 wt%, or 18 wt%, or 19 wt%, or 20 wt%, based on the total weight of the latex particles in the composition. The upper limit of the amount of the second latex polymer (b) particles can be 50 wt%, or 45 wt%, or 42 wt%, or 40 wt%, or 38 wt%, or 37 wt%, or 36 wt%, or 35 wt%, or 34 wt%, or 33 wt%, or 32 wt%, or 31 wt%, or 30 wt%, based on the total weight of the latex particles in the composition. It should be understood by those skilled in the art that any range formed by any explicitly disclosed lower and upper limits is explicitly included in this specification.
[0227] Mixed latex composition for preparing dip-molded products :
[0228] The polymer latex used to prepare the elastic film is particularly suitable for the dip molding process. Therefore, the polymer latex is compounded to generate a curable polymer latex compound composition that can be directly used in the dip molding process. In order to obtain reproducible good physical film properties, it is recommended to adjust the pH of the compounded polymer latex composition to a pH range of 7-13, preferably 10.5-13, and more preferably 11-12 with a pH adjuster to produce thin disposable gloves by dipping. In order to produce unsupported and / or supported reusable gloves, it is recommended to adjust the pH of the compounded polymer latex composition to a pH range of 8-10, preferably 8.5-9.5 with a pH adjuster. The compounded polymer latex composition contains the polymer latex of the present invention, optionally contains a pH adjuster, preferably ammonia or an alkali metal hydroxide, and optionally contains conventional additives selected from antioxidants, pigments, TiO2, fillers and dispersants for these compositions.
[0229] Alternatively, instead of compounding the polymer latex of the present invention, a polymer latex comprising the latex polymer (a) as defined above may also be compounded in the same manner as described above, and a polymer latex comprising the oxirane-functional latex polymer (b) as defined above may be added during or after the compounding step to provide the compounded latex composition of the present invention. A polymer latex comprising the oxirane-functional latex polymer (b) as defined above may also be compounded in the same manner as described above, and the polymer latex (a) as defined above may be added during or after the compounding step to provide the compounded latex composition of the present invention. Of course, all variations of the above-described latex polymer (a), oxirane-functional latex polymer (b), and relative amounts based on the total amount of latex polymer may be employed.
[0230] However, it is particularly advantageous that the use of sulphur vulcanization systems and crosslinking agents and optionally ZnO can be avoided entirely, while the polymer latex compounds used according to the present invention can still be cured to provide dip-molded articles having the desired tensile properties and self-healing properties making them repairable and / or recyclable.
[0231] Method for preparing dip-molded products:
[0232] In the method for preparing the dipped latex product according to the present invention, first, a clean mold having the desired shape of the final product is immersed in a coagulant bath including a metal salt solution. The coagulant is generally used in the form of a solution in water, alcohol or a mixture thereof. As a specific example of the coagulant, the metal salt may be a metal halide such as calcium chloride, magnesium chloride, barium chloride, zinc chloride and aluminum chloride; a metal nitrate such as calcium nitrate, barium nitrate and zinc nitrate; a metal sulfate such as calcium sulfate, magnesium sulfate and aluminum sulfate; and an acetate such as calcium acetate, barium acetate and zinc acetate. Calcium chloride and calcium nitrate are most preferred. The coagulant solution may contain additives to improve the wetting behavior of the coagulant solution.
[0233] After this, the mold is removed from the bath and optionally dried. The mold thus treated is then immersed in the mixed latex composition according to the present invention. Thus, a latex film is condensed on the mold surface. As is known in the art, the thickness of the film thus impregnated can be affected by the concentration of the mixed latex and / or the length of time the salt-coated mold is in contact with the mixed latex. Alternatively, the latex film can also be obtained by multiple impregnation steps, particularly two sequential impregnation steps.
[0234] Thereafter, the mold is removed from the latex composition and optionally immersed in a water bath in order to extract, for example, polar components from the composition and to wash the coagulated latex film.
[0235] Thereafter, the latex coated mold is optionally dried at a temperature below 80°C.
[0236] Finally, the latex-coated mold is heat-treated at a temperature of 40-180°C in order to obtain the desired mechanical properties of the final film product. The finished latex film is then removed from the mold. The duration of the heat treatment will depend on the temperature and is generally 1-60 minutes. The higher the temperature, the shorter the required treatment time.
[0237] The inventors of the present invention surprisingly found that when the polymer latex of the present invention is used, the dipping process can be carried out more economically. In particular, it was found that the duration (ripening time) between forming the compounded latex composition according to the present invention and carrying out the dipping step can be significantly reduced to 180 minutes or less, compared to the aging time required for the compound made from standard latex, which is much higher than 180 minutes.
[0238] In addition, the inventors have found that the temperature in the heat treatment step can be significantly reduced to a range of 40°C to less than 120°C without compromising the mechanical properties of the final dip-molded product. Conventional latex requires temperatures of 120°C and above to achieve the desired mechanical properties. Therefore, when the polymer latex of the present invention is used, the dip-molding process is less time-consuming and less energy-consuming, making it more economical.
[0239] Therefore, according to the present invention, it is preferred
[0240] In the mixing step (a)
[0241] (i) compounding the polymer latex according to the present invention by adjusting the pH to the range of 10.5-13, preferably 11-12 without adding ZnO; or
[0242] (ii) compounding a polymer latex comprising latex polymer (a) particles as defined above by adjusting the pH to a range of 10.5-13, preferably 11-12, without the addition of ZnO, and subsequently adding preformed latex polymer (b) particles as defined above; or
[0243] (iii) compounding a polymer latex comprising particles of polymer (b) as defined above by adjusting the pH to a range of 10.5-13, preferably 11-12, without the addition of ZnO, and subsequently adding preformed latex polymer (a) particles as defined above; and
[0244] The thus obtained compounded latex composition free of sulfur vulcanizing agent, sulfur vulcanization accelerator and ZnO is aged for less than 180 minutes, preferably 10 minutes to 150 minutes, more preferably 20 minutes to 120 minutes, most preferably 30 minutes to 90 minutes before being used in the dipping step d); and / or
[0245] - In the heat treatment step h), the latex coated mould is heat treated at a temperature of 40°C to below 120°C, preferably 60°C-100°C, more preferably 70°C-90°C.
[0246] The final heat-treated polymer latex film has a tensile strength of at least about 7 MPa and an elongation at break of at least about 300%, preferably a tensile strength of at least about 10 MPa, an elongation at break of at least about 350%, more preferably a tensile strength of at least about 15 MPa and an elongation at break of at least about 400%, and even more preferably a tensile strength of at least about 20 MPa and an elongation at break of at least about 500%. These mechanical properties are measured according to ISO 37-77 (5th edition 2011-12-15).
[0247] The present method can be used for any latex product produced by dip molding methods known in the art.
[0248] The article to which the repair or recycling method according to the invention is to be applied may be selected from healthcare equipment formed from or comprising an elastic film, surgical gloves, examination gloves, condoms, catheters or all kinds of industrial and household gloves.
[0249] Method for repairing an elastic membrane or an article comprising the elastic membrane
[0250] The articles formed by the elastic film are collected, sorted and optionally sterilized according to the purpose of treatment. Articles that are damaged but not to the extent that they cannot be reused are separated, and the damaged surface is optionally further cleaned. This cleaning can be washing with hydrogen peroxide or other sterilizing fluids or passing under a carbon dioxide gas stream or UV light to ensure that there are no pathogens. At the damaged location, the surfaces of the damaged films that are separated from each other are brought together so that they are in contact with each other, for example, if there are holes, the edges of the holes are brought into contact, the surfaces are heated so that the elastic film can soften and the surfaces are sealed together to repair the damage, and then the surfaces are cooled and the repaired or self-healed surfaces are exposed. Heating can be performed when pressure is applied to the damaged surface contact area.
[0251] Method for recycling elastic film or article containing the elastic film
[0252] Elastomeric materials such as gloves are collected and, if necessary, sorted so that the nitrile-containing materials are collected together and the other materials are discarded or sent to another recycling or reprocessing facility. The collected materials are then washed and, if necessary, decontaminated, similar to the repair / self-healing method. The material is then crushed into particles with an average diameter of no more than 2 mm, preferably an average diameter of no more than 1 mm, and an ideal diameter is a particle size with an average diameter in the range of 0.15-0.75, more preferably 0.2-0.3. The crushing or grinding process can be carried out at temperatures below room temperature or at practically low temperatures for ease of processing, and the material is kept in particles before further processing. Cold conditions are maintained to avoid recombination of the particles until they are needed for use. The material can be stored at room temperature or under such conditions to avoid recombination of the particles until they are needed for use. The material can be further ground before it is sent to a blender, where it is blended with other materials such as particles of the original elastic material and conventional processing aids and additives. If there is no blending step, the material is directly sent to a thermal treatment system where the granules / particles are hot pressed, rolled, calendered or extruded under pressure and heat, i.e. above 40°C, to make the material flowable until the glass transition temperature of the material is reached, at which stage the material can also be molded into the desired final shape. Thereafter, the material is optionally cooled in the mold or as part of the extrusion process to produce the final product formed from the recycled material.
[0253] The present invention will be further illustrated with reference to the following examples.
[0254] Determination of physical parameters:
[0255] The dispersions were characterized by determining total solids content (TSC), pH, gel content, viscosity (Brookfield LVT) and z-average particle size. In addition, the tensile properties of the final films were tested.
[0256] Determination of total solid content (TSC):
[0257] The determination of the total solid content is based on the gravimetric method. 1-2 g of the dispersion is weighed on an analytical balance into a tared aluminum dish. The dish is placed in a circulating air oven at 120°C for 1 hour until a constant mass is reached. After cooling to room temperature, the final weight is re-determined. The solid content is calculated as follows:
[0258] m 初始 –m 最终
[0259] TSC =--------------- 100% (1)
[0260] m 初始
[0261] (1) where m 初始 = initial mass of latex, m 最终 =Mass after drying
[0262] Determination of pH value:
[0263] The pH value was determined in accordance with DIN ISO 976. After a two-point calibration using a buffer solution, the electrode of a Schott CG 840 pH meter was immersed in the dispersion at 23° C. and the constant value on the display was recorded as the pH value.
[0264] Determination of viscosity:
[0265] The latex viscosity is determined at 23°C using a Brookfield LVT viscometer. About 220 ml of liquid (without bubbles) is placed in a 250 ml beaker and the viscometer's spindle is immersed up to the spindle mark. The viscometer is then turned on and the value is recorded after about 1 minute until it is constant. The viscosity range determines the choice of spindle and speed as well as the factor used to calculate the viscosity using the recorded values. Information about the spindle used and the number of revolutions per minute is shown in brackets in Examples 1, 2 and 8.
[0266] Determination of particle size (PS):
[0267] The z-average particle size was measured using a Malvern Zetasizer Nano S (ZEN 1600) with dynamic light scattering. The latex sample was diluted to the turbidity level described in the manual with deionized water and transferred to a sample cell. The sample cell was gently mixed to make the sample uniform and the sample cell was placed in the measurement device. The recorded value is the z-average particle size generated by the software.
[0268] Dip membrane preparation:
[0269] The nitrile latex with or without compounding materials was stirred at the desired pH value at room temperature for 3 hours and then impregnated with the coagulant as follows. The ceramic spatula was washed with soap, then rinsed thoroughly with deionized water, and then dried in an air circulation oven set at 65-70°C (shovel temperature, 55-60°C) until dry. The coagulant solution was prepared by dissolving calcium nitrate (18 wt%) and calcium carbonate (2 wt%) in deionized water. The dried spatula was then immersed in the salt solution, removed and then dried in an air circulation oven set at 70-75°C (shovel temperature, 60-65°C) until dry. The salt-coated spatula was then immersed in the desired compounded latex (total solids content of 18 wt% and matured at room temperature for 24 hours after compounding) for a residence time of 5 seconds, then it was removed and the latex-coated spatula was placed in an air circulation oven set at 100°C for 1 minute to gel the film.
[0270] The gelled film was then washed in a deionized water box set at 50-60°C for 1 minute and then cured in an air circulating oven set at 120°C for 20 minutes; thereafter, the thus cured / vulcanized film was cooled and removed from the spatula and then aged for 22 hours in an air circulating oven set at 100°C. Finally, the cured glove was manually peeled from the spatula, with a typical dry film thickness of 0.056-0.066 mm. The gloves prepared from the latex were tested for their tensile strength properties and stress relaxation behavior.
[0271] Determination of tensile strength properties of glove samples:
[0272] The tensile properties of the vulcanized or recycled gloves were tested according to ISO 37-77 (5th edition 2011-12-15), using an ISO 37-2 type cutter to cut dumbbell-shaped specimens (width of narrow portion = 4 mm, length of narrow portion = 25 mm, total length = 75 mm, the thickness of the dumbbell is listed in the results table) from gloves prepared from each latex compound, and tested on a Hounsfield HK10KS tensiometer equipped with a H500LC extensometer at an elongation rate of 500 mm / min.
[0273] Preparation of recovered glove membranes:
[0274] The samples for tensile testing are prepared by reassembling the cut samples of the impregnated film made from the original mixed latex, placing the small pieces of the mixture between two polished steel plates, and then hot pressing at a pressure of 13.8 MPa (2000 psi) and a temperature stated in each example (usually 100, 120, 150 or 180°C) for the number of minutes stated in each example (usually 5 minutes), followed by cooling to room temperature, and then cutting out dumbbell-shaped samples using a cutting machine ISO37-2 type die cutter specified in ISO37-77 (5th edition, 2011-12-15).
[0275] Determination of stress relaxation properties
[0276] The stress relaxation properties of the elastic film were tested by cutting dumbbell-shaped specimens (width of narrow portion = 6 mm, length of narrow portion = 33 mm, total length = 115 mm, the thickness of dumbbell is listed in the results table) from gloves prepared from each latex compound using an ASTM D412 C-type cutter. The test was conducted on a DMA Q800 dynamic mechanical analyzer supplied by TA Instruments, which was operated in "stress relaxation mode", i.e., in tension mode, wherein the specimen was strained to a value of 1% and the initial stress value (G0) was recorded. The subsequent stress value of the specimen at 1% strain was then recorded as the time (G t ) function.
[0277] The following abbreviations are used in the examples:
[0278] BA = n-butyl acrylate
[0279] MAA = Methacrylic Acid
[0280] Bd = Butadiene
[0281] ACN = Acrylonitrile
[0282] GMA = Glycidyl Methacrylate
[0283] tDDM = tert-dodecyl mercaptan
[0284] Na4 EDTA = Tetrasodium salt of ethylenediaminetetraacetic acid
[0285] tBHP = tert-butyl hydroperoxide
[0286] TSC = Total Solids Content
[0287] PS = particle size
[0288] ZnO=zinc oxide
[0289] ZDEC = Zinc diethyl dithiocarbamate
[0290] Unless otherwise specified, hereinafter all parts and percentages are by weight. Example
[0291] Example 1: Preparation of carboxylated nitrile latex
[0292] 2 parts by weight (based on polymer solids) of ethylene oxide-free seed latex (average particle size 36 nm) and 80 parts by weight of water (based on 100 parts by weight of the monomers including the seed latex) were added to a nitrogen-purged autoclave, followed by heating to 30° C. Then, 0.01 parts by weight of Na4 EDTA and 0.005 parts by weight of EDTA dissolved in 2 parts by weight of water were added. FF6, followed by the addition of 0.08 parts by weight of sodium persulfate dissolved in 2 parts by weight of water. Then, the monomers (35 parts by weight of acrylonitrile, 58 parts by weight of butadiene, 5 parts by weight of methacrylic acid) were added together with 0.6 parts by weight of tDDM over a period of 4 hours. Over a period of 10 hours, 2.2 parts by weight of sodium dodecylbenzene sulfonate, 0.2 parts by weight of tetrasodium pyrophosphate, and 22 parts by weight of water were added. 0.13 parts by weight of FF6 is fed with a co-activator in 8 parts by weight of water for 9 hours. The temperature is maintained at 30°C until the conversion is 95% and the total solid content obtained is 45%. The polymerization is stopped by adding 0.08 parts by weight of a 5% aqueous solution of diethylhydroxylamine. The pH is adjusted to pH 7.5 using potassium hydroxide (5% aqueous solution) and residual monomers are removed by vacuum distillation at 60°C. 0.5 parts by weight of Wings tay L-type antioxidant (60% aqueous dispersion) is added to the original latex and the pH is adjusted to 8.2 by adding 5% aqueous potassium hydroxide solution.
[0293] For Example 1, the following characterization results were obtained:
[0294] TSC = 44.9 wt%
[0295] pH=8.2
[0296] Viscosity = 38mPas (1 / 60)
[0297] Particle size, P z =121nm
[0298] Example 2: Preparation of ethylene oxide functional latex
[0299] 2.0 parts by weight of diphenyl oxide disulfonate dissolved in 185 parts by weight of water were charged to a nitrogen-purged autoclave relative to 100 parts by weight of monomers and heated to a temperature of 70°C. 0.1 parts by weight of tDDM and 0.05 parts by weight of Na4EDTA were added to the initial charge together with 0.7 parts by weight of ammonium persulfate (12% aqueous solution) in equal portions. Subsequently, a solution of 45.4 parts by weight of butadiene, 14.6 parts by weight of acrylonitrile and 5.0 parts by weight of diphenyl oxide disulfonate dissolved in 50 parts by weight of water was added over a period of 6.5 hours. 40 parts by weight of GMA were added after 1 hour, which lasted for 6.5 hours. After the addition of the monomers, the temperature was maintained at 70°C. The polymerization was maintained until the conversion was 99%. The reaction mixture was cooled to room temperature and sieved through a filter (90 μm).
[0300] For Example 2, the following characterization results were obtained:
[0301] TSC = 37.7 wt%
[0302] pH=7.1
[0303] Viscosity = 15mPas (1 / 60)
[0304] Particle size, P z =39nm
[0305] Example 3: (Comparative Example)
[0306] A portion of the XNBR latex without ethylene oxide (Example 1) was adjusted to pH 10 with aqueous potassium hydroxide solution and compounded with 1 phr zinc oxide, 1 phr titanium dioxide, 0.8 phr sulfur and 0.7 phr ZDEC. The compound was then adjusted to a solid concentration of 18 wt% and stirred for 3 hours.
[0307] Embodiment 4:
[0308] An aliquot of Example 2 (ethylene oxide functional latex) was added to an aliquot of Example 1 (XNBR latex without ethylene oxide) to provide a wet weight blend ratio of Example 1:Example 2 of 90:10.
[0309] Preparation of dip-coated samples:
[0310] Example 5 (Comparative Example)
[0311] The dried salt-coated spatula was then dipped into the compounded latex solution (Example 3) with a dwell time of 5 seconds, followed by gelling the film at 100°C for 1 minute, washing with deionized water for 1 minute (in an oven set at 50-60°C) for 1 minute, and then drying and curing / vulcanizing in an air circulating oven set at 120°C for 20 minutes to ensure complete drying and crosslinking.
[0312] Embodiment 6:
[0313] The blend of Example 4 was adjusted to pH 10 with potassium hydroxide solution and the blend was stirred for 3 hours before being dipped with a dry salt coated spatula and treated according to the protocol given in Example 5.
[0314] Embodiment 7:
[0315] The blend of Example 4 was adjusted to pH 10.0 with potassium hydroxide solution and compounded with zinc oxide (1 phr), after which the blend was stirred for 3 hours before being impregnated with a dry salt-coated spatula and treated according to the protocol given in Example 5.
[0316] Embodiment 8:
[0317] The blend of Example 4 was adjusted to a pH of 11.5 with potassium hydroxide solution and then the blend was stirred for 3 hours before being impregnated with a dry salt-coated spatula and treated according to the protocol given in Example 5.
[0318] Stress relaxation test
[0319] A number of samples were tested for stress relaxation as a function of time. The samples were prepared according to the "Impregnated Film Preparation" section above.
[0320] Embodiment 9:
[0321] Subsequently, the dried solidified film obtained from Example 5 (Comparative) was cut into a number of dumbbell-shaped samples (25 ± 0.8 mm long, 6 mm wide and 0.056-0.066 mm thick) using a preform cutting machine (see Figure 1 ).
[0322] The dumbbell-shaped sample was then clamped into the jaws of a DMA Q800 dynamic mechanical analyzer supplied by TA Instruments and the sample was allowed to equilibrate at the test temperature for 5 minutes, then strained to 1% and the initial stress value was recorded as G0 (see Figure 2 The strain was maintained at 1%, and the stress value (G t ), usually lasting 1200 seconds (see Figure 3 ).
[0323] Typical test temperatures selected were 100, 120, 150 and 180°C.
[0324] Stress relaxation is defined as follows,
[0325] Stress relaxation = G t / G0
[0326] The results obtained in Example 9 are shown in Figure 4 The thickness of the specimen is shown in brackets on the figure; it should be noted that t A line is drawn at the value of / G0=1 / e(=0.63).
[0327] refer to: ht tp: / / web.mi t.edu / course / 3 / 3.11 / www / modules / visco.pdf
[0328] The time taken for the stress to reach the 1 / e value is listed in Table 1 below. The stress relaxation values at 120 and 100°C did not drop below the 1 / e value.
[0329] Example 10
[0330] This is exactly the same as Example 9, except that Example 6 is replaced by Example 5. The results are shown in Figure 5 and Table 1.
[0331] Figure 5 The results of the stress relaxation experiments are given in Table 3.
[0332] This data shows that the data at 100°C does not drop below the 1 / e value; in addition, contrary to Example 9, the data shows a decreasing trend with temperature.
[0333] Embodiment 11:
[0334] This is exactly the same as Example 9 except that Example 8 is replaced by Example 5; the results are shown in Figure 6 and Table 1.
[0335] This data shows that for the zinc oxide-free elastomeric system compounded to pH 11.5, the rate of change of stress relaxation values decreases in the order 180>>150>120>100°C, and all data sets reach the 1 / e value.
[0336] Table 1
[0337]
[0338] This data demonstrates the reprocessability of the elastic films prepared according to the present invention. It is believed that this data can be interpreted as, compared to the comparative examples, in the examples of the present invention, the crosslinks are broken and the polymer system can then move on a microscopic scale to relieve the applied stress. At higher temperatures, this effect is more pronounced. The elastic films prepared without ZnO also show this effect at lower temperatures. This result demonstrates the self-healing properties of the elastic films described herein.
[0339] Recycling of elastic membranes
[0340] Several elastic films were recovered and the tensile strength values of the initial elastic films were compared with the tensile strength values of the recovered films.
[0341] Example 12: (Comparative Example) and 13-15
[0342] Using the 2-type dumbbell cutter die specified in ISO37 (5th edition, 2011-12-15), the film prepared according to Examples 5-8 was cut into samples for tensile testing. The end of the dumbbell was placed in the jaws of a Hounsfield HK10KS tensiometer equipped with a H500LC extensometer and stretched at a strain rate of 500 mm / min. Stress values were automatically reported by the machine software, as were modulus values at given strains (usually 100, 300 and 500% strain). The results are reported in Table 2.
[0343] Table 2
[0344]
[0345] Recycling of elastic membranes
[0346] Herein, a recyclable elastic film is defined as an elastic film which, after being cut into small pieces, can be reassembled after subjecting the small pieces to low temperature, typically less than 100°C for 1 minute, or preferably at 80°C for 5 minutes, under an applied pressure of 13.8 MPa (2000 psi), and thereafter exhibits an elongation at break of more than 90% and a tensile strength of more than 1.5 MPa according to the following test protocol.
[0347] Embodiment 16: (comparative example)
[0348] The samples for tensile testing were prepared by reassembling cut samples of the impregnated film made from compounded latex Example 5 (Comparative Example) (the original film was prepared according to the protocol of Example 5), annealing the small piece of the mixture between two polished steel plates, and then hot pressing at 13.8 MPa (2000 psi) and 100°C for 1 minute, followed by cooling to room temperature and then cutting dumbbell-shaped samples using a type 2 die cutter as specified in ISO37 (5th edition, 2011-12-15). The ends of the dumbbell-shaped samples were placed in the jaws of a Hounsfield HK10KS tensiometer equipped with a H500LC extensometer and stretched at a strain rate of 500 mm / min. Stress values were automatically reported by the machine software, as were modulus values at given strains (usually 100, 300 and 500% strain). The results are reported in Table 3.
[0349] Embodiment 17:
[0350] This is exactly the same as Example 16 except that Example 6 replaces Example 5 and the results are reported in Table 3.
[0351] Example 18: (Comparative Example)
[0352] This is exactly the same as Example 16, except that the dumbbell samples were annealed at 13.8 MPa (2000 psi) and 80°C for 5 minutes, cooled to room temperature and the ends of the dumbbell samples were placed in the jaws of a Hounsfield HK10KS tensiometer equipped with a H500LC extensometer and stretched at a strain rate of 500 mm / min. Stress values were automatically reported by the machine software, as were modulus values at given strains (typically 100, 300 and 500% strain). The results are reported in Table 3.
[0353] Embodiment 19
[0354] This is exactly the same as Example 18, except that Example 6 replaces Example 3; the results are shown in Table 5.
[0355] Embodiment 20
[0356] This is exactly the same as Example 18, except that Example 8 replaces Example 5; the results are shown in Table 3.
[0357] Table 3
[0358]
[0359] Where F = failure / fracture of sample
[0360] Table 3 shows that the comparative examples (16 and 18) all failed (dumbbell-shaped sample fracture) at a strain less than 100%, and all showed a tensile strength less than 1.5 MPa and an elongation at break less than 90 strain; therefore, the comparative examples did not show the ability to self-heal at the annealing temperature used.
[0361] After annealing at 100° C. for 1 minute or 80° C. for 5 minutes, Examples 17 and 19 (without zinc oxide, pH 10.0) showed a tensile strength exceeding 3 MPa and an elongation at break exceeding 200%. That is, the films made from these dipped gloves are recyclable films.
[0362] Example 20 shows that increasing the pH to 11.5 increases the tensile strength and modulus, although the elongation at break decreases to 139%. That is, the film made from the dipped glove is a recyclable film.
[0363] Determination of tensile properties after repairing the elastic membrane:
[0364] The nitrile latex with or without compounding materials at the desired pH was stirred at room temperature for 3 hours and then cast onto a Petri dish.
[0365] The cast latex film on the petri dish surface was then placed in a circulating air oven at 25° C. for three days. The resulting film was then annealed in an air circulating oven at 90° C. for 24 hours to ensure complete drying and any desired cross-linking.
[0366] The cast membrane was carefully removed from the glass dish and cut into dumbbell shapes using a 3 mm 'D' cutter (see Figure 1 ). One dumbbell-shaped sample was left uncut (as a control sample), while the other dumbbell-shaped sample was cut in half at the midpoint (see Figure 2 If necessary, mark the top surface of each cut half for reference. The newly cut dumbbell-shaped specimen surfaces are then immediately pressed together for 60 seconds (see Figure 3 ) and the slices were placed on a glass plate, and the rejoined pieces on the glass plate were then placed in an air circulating oven at 180°C for 30 minutes (simulating a heat treatment process for pressure-free drying glue). Alternatively, the newly cut dumbbell surfaces were then immediately pressed together for 60 seconds, and the pressure was maintained by placing the "jaws" of a wooden clamp on the rejoined parts, followed by heat treatment at 180°C in an oven for 30 minutes. This was intended to simulate a low-pressure drying glue heat pressing process.
[0367] Example 21 (Comparative Example)
[0368] A portion of the XNBR latex (Example 1) containing no ethylene oxide was adjusted to a pH of 10 with an aqueous potassium hydroxide solution and compounded with 1 phr zinc oxide, 0.8 phr sulfur and 0.7 phr ZDEC. The compound was then stirred for 3 hours, then cast onto a glass petri dish and allowed to dry at room temperature (25° C.) for 3 days. The film obtained was removed from the glass petri dish and annealed in an oven at 90° C. for 24 hours to ensure complete drying and formation of crosslinks.
[0369] Membranes in which a membrane that is cut in half and subsequently brought together is able to exhibit tensile strength upon subsequent separation of the so joined halves are referred to as self-healing.
[0370] Subsequently, stress-strain analysis was performed on two dumbbell samples (cut and rejoined and uncut) to determine the tensile properties of the elastomer before and after cutting and rejoining. That is, to determine the degree of self-healing of the cut film. Tensile properties were tested using a tensile test of a 3 mm 'D' dumbbell specimen according to ASTM D412-06a, with a typical film thickness of 1.0-1.4 mm ± 0.01 for self-cast latex film cutting. The film thickness (mm) was measured using a thickness gauge (supplied by Sylvac, model Studenroth, type 12.5 mm / 0.001).
[0371] Tensile stress-elongation curves were recorded using a Zwick Roel Z005 TN Proline tensiometer equipped with a long-stroke extensometer. The samples were elongated at a rate of 500 mm / min at a temperature of 23 ± 2 °C and a relative humidity of 50 ± 5%. The tensile strength data reported here correspond to the maximum tensile stress observed during the elongation of the dumbbell to break. The reported ultimate elongation values correspond to the elongation at which break occurred. The reported modulus values M 100 、M 300 and M 500 Corresponds to the stress required to achieve an elongation of 100%, 300% or 500% of the original length respectively.
[0372] Preparation of dumbbell samples and comparison of uncut and self-healed samples:
[0373] Embodiment 22:
[0374] The dried and cured film obtained from Example 21 was then cut into a plurality of dumbbell samples using a 'D' cutter (see Figure 1 ). One dumbbell remains uncut while the other is cut in half using a sharp blade applied to the narrow part of the dumbbell (see Figure 2 ). The cut dumbbells were then immediately rejoined by holding the cut surfaces together and manually pressing them together for 60 seconds (see Figure 3). The dumbbells thus rejoined were then annealed for 30 minutes in an air circulating oven maintained at 180° C. The self-healed dumbbells were then subjected to tensile testing to determine the extent of recovery of tensile properties by comparison with the results obtained with uncut dumbbells obtained from the same cast film.
[0375] The results are shown in Table 4 and Figure 7 middle.
[0376] Embodiment 23
[0377] An aliquot of Example 2 (ethylene oxide functional latex) was added to an aliquot of Example 1 (XNBR latex without ethylene oxide) to make a wet weight blend ratio of Example 1: Example 2 of 90:10. The blend was adjusted to a pH of 10 with potassium hydroxide solution, stirred for 3 hours, then cast onto a glass petri dish, and allowed to dry at room temperature (25°C) for 3 days. The obtained film was removed from the glass petri dish and annealed in an oven at 90°C for 24 hours to ensure complete drying and crosslinking. The film was then cut into dumbbell shapes and tested according to Example 22.
[0378] The results are shown in Table 4 and Figure 8 middle.
[0379] Embodiment 24
[0380] This was a repeat of Example 23 except that 1 phr zinc oxide was added to the latex at pH 10 and stirred for 3 hours prior to casting. The membranes were then cut into dumbbell shapes and tested as in Example 22.
[0381] The results are shown in Table 4 and Fig. 9 middle.
[0382] Embodiment 25
[0383] This was a repeat of Example 23, except that the pH was adjusted to 11.5. The membranes were then cut into dumbbell shapes and tested as in Example 22.
[0384] The results are shown in Table 4 and Fig.10 middle.
[0385] Table 4
[0386]
[0387]
[0388] Embodiment 26
[0389] An aliquot of Example 2 (ethylene oxide functional latex) was added to an aliquot of Example 1 (XNBR latex without ethylene oxide) to provide a wet weight blend ratio of Example 1:Example 2 of 90:10.
[0390] The blend was adjusted to a pH of 5 with potassium hydroxide solution, stirred for 3 hours, then cast onto a glass petri dish, and allowed to dry at room temperature (25°C) for 3 days. The obtained film was removed from the glass plate and annealed in an oven at 90°C for 24 hours to ensure complete drying and crosslinking. The dried and cured film was then cut into several dumbbell-shaped samples using a 'D' cutter. One dumbbell-shaped sample remained uncut, while another was cut in half using a sharp blade to cut the narrow portion of the dumbbell-shaped sample. Subsequently, the cut surfaces were immediately held together and manually pressed together for 60 seconds to rejoin the cut dumbbell-shaped samples, followed by the jaws of a wooden clothespin to maintain close contact between the two surfaces, so that the dumbbells so rejoined were annealed in an air circulation oven maintained at 180°C for 30 minutes. The results are shown in Table 5.
[0391] Embodiment 27
[0392] This was a repeat of Example 26 except that the pH was adjusted to 10. The results are shown in Table 5.
[0393] Embodiment 28
[0394] This was a repeat of Example 26 except that the pH was adjusted to 11.
[0395] The results are shown in Table 5.
[0396] Embodiment 29
[0397] This was a repeat of Example 26 except the pH was adjusted to 11.5.
[0398] The results are shown in Table 5.
[0399] Table 5
[0400]
[0401]
Claims
1. A method for repairing an elastic film or a product comprising the elastic film by the following steps: a) providing a damaged elastic film or an article comprising a damaged elastic film, wherein the damaged elastic film has at least a surface to be reconnected, b) rejoining the surfaces of the damaged membrane, and c) heating or annealing the damaged elastic film at a temperature of 40° C. to 200° C. while maintaining the rejoined surfaces of the damaged film in close contact, wherein The elastic film is made of a polymer latex comprising: (a) Particles of a carboxylated conjugated diene nitrile latex polymer (a), which can be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: -15 - 99 wt% of a conjugated diene; -1 - 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds; -0.05 - 10 wt% of ethylenically unsaturated carboxylic acid and / or its salt; -0 to 50 wt% of a vinyl aromatic monomer; and -0 to 65 wt% of an alkyl ester of an ethylenically unsaturated acid, The weight percentage is based on the total monomers in the mixture. Combined or combined with: (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b).
2. The method of claim 1, wherein the damage is selected from the group consisting of a pinhole, a cut, a break, and a complete separation of the elastic film into at least two parts.
3. The method of any one of the preceding claims, wherein the temperature is from 60°C to 200°C.
4. A method for recovering an elastic film or an article comprising an elastic film, said method comprising forming elastomer particles by cutting, shredding or pulverizing said elastic film or article, optionally blending the obtained particles with particles of original elastomer, and forming the recovered film or article by subjecting the particles to a pressure of 1 to 20 MPa and a temperature of 40° C. to 200° C., wherein The elastic film is made of a polymer latex comprising: (a) Particles of a carboxylated conjugated diene nitrile latex polymer (a), which can be obtained by free radical emulsion polymerization of a mixture of ethylenically unsaturated monomers comprising: -15 - 99 wt% of a conjugated diene; -1 - 80 wt% of a monomer selected from ethylenically unsaturated nitrile compounds; -0.05 - 10 wt% of ethylenically unsaturated carboxylic acid and / or its salt; -0 to 50 wt% of a vinyl aromatic monomer; and -0 to 65 wt% of an alkyl ester of an ethylenically unsaturated acid, The weight percentage is based on the total monomers in the mixture. Combined or combined with: (b) particles of a latex polymer (b) comprising at least one oxirane functional group; wherein The monomer composition of latex polymer (a) is different from the monomer composition of latex polymer (b).
5. The method of claim 4, wherein the temperature is 60°C - 200°C, and / or the pressure is 12 - 15 MPa.
6. The method of claim 1, 2, 4 or 5, wherein (a) the conjugated diene is selected from butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene, laurylene, ocimene, farnasene and combinations thereof; (b) an ethylenically unsaturated nitrile compound selected from the group consisting of (meth)acrylonitrile, α-cyanoethylacrylonitrile, fumaronitrile, α-chloronitrile, and combinations thereof; (c) ethylenically unsaturated carboxylic acids and salts thereof selected from - monocarboxylic acids and their salts, - ethylenically unsaturated polycarboxylic acids and their salts; - partial esters of polycarboxylic acids and their salts; and d) a vinyl aromatic monomer selected from the group consisting of styrene, α-methylstyrene, vinyltoluene, and combinations thereof; e) an alkyl ester of an ethylenically unsaturated acid selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl methacrylate, n-butyl (meth)acrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and combinations thereof; The mixture of ethylenically unsaturated monomers used in the latex polymer (I) optionally comprises ethylenically unsaturated monomers selected from: f) hydroxyalkyl esters of ethylenically unsaturated acids; g) amides of ethylenically unsaturated acids; h) vinyl carboxylates; i) a monomer having at least two ethylenically unsaturated groups; j) ethylenically unsaturated silanes; and combinations thereof.
7. The process of claim 1, 2, 4 or 5 wherein the mixture of ethylenically unsaturated monomers used in latex polymer (a) comprises: -20 - 99 wt% of a conjugated diene; -1 - 60 wt% of a monomer selected from ethylenically unsaturated nitrile compounds; -0 - 40 wt% of vinyl aromatic monomer; -0 - 25 wt% of C1-C8 alkyl (meth)acrylate; -0.05 - 7 wt% of ethylenically unsaturated acid; -0 - 10wt% of vinyl ester: - 0 to 10 wt% of ethylenically unsaturated compounds with silane, amide and / or N-methylolamide groups, Weight percentages are based on the total monomers present in the mixture.
8. The method of claim 1, 2, 4 or 5, wherein the ethylene oxide functional latex polymer (b) comprises structural units derived from ethylenically unsaturated ethylene oxide functional monomers in an amount of 1 to 80 weight percent, based on the total weight of monomers in the ethylene oxide functional latex particles (b).
9. The method of claim 1, 2, 4 or 5, wherein the ethylene oxide functional latex polymer (b) comprises structural units derived from: (I) -0 - 50 wt% of a monomer selected from ethylenically unsaturated nitrile compounds; - 0 - 95 wt% of vinyl aromatic monomer; -0 - 95 wt% of C1-C8 alkyl (meth)acrylate; - 0 - 10 wt% of ethylenically unsaturated acids; - 0 to 10 wt% of ethylenically unsaturated compounds having silane groups, sulfonate groups, sulfonic acid groups, amide groups and / or N-methylolamide groups; - 0 - 50 wt% of vinyl carboxylate; - 1 to 80 wt% of structural units derived from ethylenically unsaturated oxirane-functional monomers; or (II) - 2 - 95 wt% of a conjugated diene; - 1 - 50 wt% of a monomer selected from ethylenically unsaturated nitrile compounds; - 0 - 95 wt% of vinyl aromatic monomer; - 0 - 95 wt% of C1-C8 alkyl (meth)acrylate; - 0 - 10 wt% of ethylenically unsaturated acids; - 0 to 10 wt% of ethylenically unsaturated compounds having silane groups, sulfonate groups, sulfonic acid groups, amide groups and / or N-methylolamide groups; - 1 to 80 wt% of structural units derived from ethylenically unsaturated oxirane-functional monomers.
10. The method of claim 1, 2, 4 or 5, wherein to prepare the polymer latex (i) a mixture of ethylenically unsaturated monomers for latex polymer (a) is polymerized in a free radical emulsion polymerization in the presence of particles of ethylene oxide functional latex polymer (b); or (ii) wherein a polymer latex comprising particles of latex polymer (a) and a polymer latex comprising particles of latex polymer (b) are preformed and the two latexes are subsequently combined; or (iii) a mixture of ethylenically unsaturated monomers for latex polymer (a) is polymerized in a free radical emulsion polymerization in the presence of ethylene oxide functional latex polymer (b) particles to form a first polymer latex, and a second polymer latex comprising latex polymer (b) particles is preformed and the two latexes are subsequently combined, wherein the latex comprising ethylene oxide functional latex particles (b) used to prepare the first polymer latex and the second polymer latex comprising latex polymer (b) particles are the same or different.
11. The method of claim 1, 2, 4 or 5, wherein the z-average particle size of the ethylene oxide functional latex particles (b) is 5 to 90 nm as measured by a Malvern zetasizer nano S (ZEN 1600) using dynamic light scattering.
12. The method of claim 1, 2, 4 or 5, wherein the elastic film or the article comprising the elastic film is made from a compounded latex composition comprising a polymer latex free of sulfur vulcanizing agents and sulfur vulcanization accelerators as defined in any one of claims 1, 4 and 6 to 11, and optionally treated with one or more of the following properties: - the compounded latex composition does not contain ZnO; - The pH of the compounded latex composition is 10.5 - 13.
13. The method of claim 12, wherein the article is prepared by a dip molding process comprising: a) providing a compounded latex composition as defined in claim 12; b) immersing a mold having the desired shape of the final product into a coagulant bath comprising a metal salt solution; c) removing the mold from the coagulant bath and optionally drying the mold; d) dipping the mold treated in steps b) and c) into the compounded latex composition of step a); e) coagulating a latex film on the surface of the mold; f) removing the latex-coated mold from the compounded latex composition and optionally immersing the latex-coated mold in a water bath; g) optionally drying the latex-coated mold; h) heat treating the latex coated mold obtained from step e) or f) at a temperature of 40°C to 180°C; and i) Removing the latex object from the mold.
14. The method of claim 1, 2, 4 or 5, wherein the article comprising the elastic film is selected from the group consisting of surgical gloves, examination gloves, condoms, catheters, industrial gloves, textile-supported gloves, and household gloves.
15. Use of a polymer latex as defined in any one of claims 1, 4 and 6 to 11 or a compounded latex composition as defined in claim 12 to make an elastic film obtained from said polymer latex self-healing, repairable and / or recyclable.
Citation Information
Patent Citations
Process for preparing a latex based on conjugated dienes by emulsion polymerization
EP0792891A1
Polymer latex for dip-molding applications
WO2017209596A1
Polymer latex for dip-molding applications
CN109379893A